Pengaruh Cooking Class Berbasis Budaya Melayu terhadap Perkembangan Kognitif Anak Usia Dini Usia 5-6 Tahun di TK Negeri Pembina Sungai Mandau - Ulfa Maharani; Yesi Novitasari (Lembaga Yasin AlSys, 2026)
Early childhood cognitive development should be stimulated through concrete and active learning that is consistent with children’s experiences and cultural environments. However, learning dominated by conventional activities may limit children’s opportunities to explore, solve problems, and develop thinking skills through direct experience. This study aims to analyze the effect of a Malay culture-based cooking class method on the cognitive development of children aged 5–6 years at TK Negeri Pembina Sungai Mandau. The study employed a quantitative approach with a quasi-experimental design involving 24 children, comprising 12 children from class B4 as the experimental group and 12 children from class B2 as the control group. Data were collected through observation using an instrument comprising 10 indicators of cognitive development rated on a scale of 1–4. The experimental group received three treatments involving the preparation of Minuman Laksamana Mengamuk, Kue Kemojo, and Roti Jala, whereas the control group participated in conventional learning. The data were analyzed using tests of normality and homogeneity and an independent-samples t test. The findings indicate that the experimental group’s mean cognitive ability score increased from 45.00 on the pretest to 88.95 on the posttest, representing an increase of 43.95 points. Meanwhile, the control group’s mean score increased from 46.87 to 53.54, representing an increase of 6.67 points. The test results revealed a significant difference between the two groups (t = 14.242; p < .001). This study concludes that Malay culture-based cooking classes significantly affect the cognitive development of children aged 5–6 years by facilitating concrete experiences, exploration, problem-solving, creativity, and the introduction of local wisdom. These findings contribute to the development of contextual learning in early childhood education and provide practical implications for teachers seeking to integrate local culture-based cooking activities into learning activities.